BRONJ in patients with rheumatoid arthritis: a multicenter case series. (27th May 2016) - Di Fede, O; Bedogni, A; Giancola, F; Saia, G; Bettini, G; Toia, F; D'Alessandro, N; Firenze, A; Matranga, D; Fedele, S; Campisi, G
Abstract : Objective: Osteonecrosis of the jaw (ONJ) is a potentially severe adverse effect of various medications (bisphosphonates, anti‐resorptive, and anti‐angiogenic drugs). ONJ pathogenesis is still unclear although some risk factors have been recognized. Of these, rheumatoid arthritis (RA) has been hypothesized as a potential risk factor for developing ONJ. This observational study will describe a multicenter case series of patients affected with RA and ONJ, and it will attempt to evaluate the association between features of ONJ and pharmacological, systemic, and site variables. Methods: Demographic, pharmacological, and clinical data from 18 RA patients with ONJ were collected and registered from three Italian centers (i.e., Palermo, Verona, and Padua) from 2004 to 2013. Results: Sixteen (88.9%) patients were in therapy for RA: 9 of 18 (50.0%) with systemic steroids, 3 of 18 (16.7%) with methotrexate, and 4 of 18 (22.2%) with both medications. Two patients were not receiving treatment for RA. All patients took NBPs for secondary osteoporosis (average NBP duration of 69 months, range: 20–130): Fifteen (83.3%) patients were treated with single NBPs, while three (16.7%) with different molecules; one patient was also treated with denosumab. Mandible was affected more frequently (66.7%) than maxilla (33.3%); one patient presented multiple ONJ events. Conclusions: This is the first multicenter case series in the international literature regarding our topic. Focusing on our data, it could be hypothesized that patients with RA may be more susceptible to ONJ than the majority of osteometabolic patients. In our opinion, it could be important to monitor also denosumab or other biological drug side effects.